LMC CONTACT PROGRAM...DRAFT PROPOSAL (Tufts Archival Research Center, 2007)
Summary of the Labor Management Committee (LMC) contact program which is involved in garnering support among the labor unions to oppose the tobacco settlement. Suggests strategies and tactics for reaching out to the unions.